If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 25 = -14 Reorder the terms: 25 + 13x = -14 Solving 25 + 13x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 13x = -14 + -25 Combine like terms: 25 + -25 = 0 0 + 13x = -14 + -25 13x = -14 + -25 Combine like terms: -14 + -25 = -39 13x = -39 Divide each side by '13'. x = -3 Simplifying x = -3
| 2.5(x-16)=-6 | | 4*4-y=38-5*5 | | .9(-.8)-1.3=-1.3 | | 10.6-2.6x-6.24=11-3x-6 | | 0.01/(0.1x-10x^2) | | [8(x+5)-18]+[3(x-3)+1]= | | 9.10(x+8)=18 | | .9(.8)-1.3=-1.3 | | 14x-9y=45 | | 4.9(x+13)=8 | | [5+(-3)]+2=5+[(-3)+2] | | P(p+1)=132 | | P(p+1)=12 | | [7(m+5)-15]+[3(m-2)+2]= | | H=16t^2+75t+4 | | X^5y^4/3xy/1/x^3y | | x+71+x+92=89 | | X^2-9/x-3=5 | | 6sin^2(x)-sin(X)-1=0 | | 5p+7=12+3p | | 186=2x | | X(5x+8)(7x-3)=0 | | -36x=-720 | | -70x=-560 | | 126=x+92 | | 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 |